Features of Addiction Propensity and Emotional Intelligence in Graduates of Physics and Mathematics Classes - S.S. Romantcheva; O.R. Busarova (Психология и право)
The article examines the tendency to different types of addictive behavior in graduates of physics and mathematics classes. The sample consisted of 89 young men and women aged 18-26 years, the main group - graduates of physics and mathematics classes, 49 people, prize winners or winners of significant Olympiads; the control group - graduates of classes of other profiles or non-core classes, 40 people. The purpose of the study is to identify the features of the inclinations to different types of addictive behavior of male graduates of physics and mathematics classes, the hypothesis of the study: graduates of physics and mathematics classes are more prone to workaholism and computer addiction than their peers. The tendency to 13 types of addictions was assessed using the method of G.V. Lozovaya, emotional intelligence was additionally assessed using the method of N. Hall. It turned out that graduates of physics and mathematics classes are more vulnerable in terms of their tendency to a number of addictions; in this group, multiple significant correlations were found between the tendency to various addictions and aspects of emotional intelligence, which allows us to consider the development of emotional intelligence of graduates of physics and mathematics classes as a means of reducing their tendency to addictive behavior.